Chronic Kidney Disease and Arterial Stiffness: A Two-Way Path - Inserra, Felipe; Forcada, Pedro; Castellaro, Agustina; Castellaro, Carlos (Frontiers in Medicine, 2021)
The kidney-heart relationship has raised interest for the medical population since its vast and complex interaction significantly impacts health. Chronic kidney disease (CKD) generates vascular structure and function changes, with significant hemodynamic effects. The early arterial stiffening in CKD patients is a consequence of the interaction between oxidative stress and chronic vascular inflammation, leading to an accelerated deterioration of left ventricular function and alteration in tissue perfusion. CKD amplifies the inflammatory cascade's activation and is responsible for altering the endothelium function, increasing the vascular tone, wall thickening, and favors calcium deposits in the arterial wall. Simultaneously, the autonomic imbalance, and alteration in other hormonal systems, also favor the overactivation of inflammatory and fibrotic mediators. Thus, hormonal disarrangement also contributes to structural and functional lesions throughout the arterial wall. On the other hand, a rise in arterial stiffening and volume overload generates high left ventricular afterload. It increases the left ventricular burden with consequent myocardial remodeling, development of left ventricular hypertrophy and, in turn, heart failure. It is noteworthy that reduction in glomerular mass of renal diseases generates a compensatory glomerular filtration overdriven associated with large-arteries stiffness and high cardiovascular events. Furthermore, we consider that the consequent alterations of the arterial system's mechanical properties are crucial for altering tissue perfusion, mainly in low resistance. Thus, increasing the knowledge of these processes may help the reader to integrate them from a pathophysiological perspective, providing a comprehensive idea of this two-way path between arterial stiffness and renal dysfunction and their impact at the cardiovascular level.